Acute kidney injury from contrast-enhanced CT procedures in patients with cancer: white paper to highlight its clinical relevance and discuss applicable preventive strategies - Cosmai, Laura (ESMO Open, 2020)
Patients with cancer are subjected to several imaging examinations which frequently require the administration of contrast medium (CM). However, it has been estimated that acute kidney injury (AKI) due to the injection of iodinated CM accounts for 11% of all cases of AKI, and it is reported in up to 2% of all computed tomography (CT) examinations. Remarkably, the risks of developing AKI are increased in the elderly, in patients with chronic kidney disease or diabetes, and with dehydration or administration of nephrotoxic chemotherapeutics. Given the common occurrence of post-contrast acute kidney injury (PC-AKI) in clinical practice, primary care physicians and all specialists involved in managing patients with cancer should be aware of the strategies to reduce the risk of this event. In 2018, a panel of five experts from the specialties of radiology, oncology and nephrology were speakers at the annual meeting of the Italian Society of Medical Radiology (Società Italiana di Radiologia Medica e Interventistica), with the aim of commenting on existing evidence and providing their experience on the incidence and management of PC-AKI in patients with cancer. The discussion represented the basis for this white paper, which is intended to be a practical guide organised by statements describing methods to reduce renal injury risks related to CM-enhanced CT examinations in patients with cancer.